2019
DOI: 10.1021/acsomega.9b02291
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Annealing Temperature and Ambient on Metal/PtSe2 Contact Alloy Formation

Abstract: Forming gas annealing is a common process step used to improve the performance of devices based on transition-metal dichalcogenides (TMDs). Here, the impact of forming gas anneal is investigated for PtSe2-based devices. A range of annealing temperatures (150, 250, and 350 °C) were used both in inert (0/100% H2/N2) and forming gas (5/95% H2/N2) environments to separate the contribution of temperature and ambient. The samples are electrically characterized by circular transfer length method structures, from whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 47 publications
(69 reference statements)
1
9
0
Order By: Relevance
“…Low levels of PtS were found to be almost ever present in all of the PtS2 films synthesised here. A third component with 4 7 2 ⁄ at ~75.4 eV is fitted, assignment of this low intensity and broad doublet is difficult and it is provisionally assigned as a Pt-oxide due to the binding energy of the peaks, this aligns with previous interpretations for PtSe2 56 .…”
Section: Xps Of Pts and Pts2supporting
confidence: 78%
“…Low levels of PtS were found to be almost ever present in all of the PtS2 films synthesised here. A third component with 4 7 2 ⁄ at ~75.4 eV is fitted, assignment of this low intensity and broad doublet is difficult and it is provisionally assigned as a Pt-oxide due to the binding energy of the peaks, this aligns with previous interpretations for PtSe2 56 .…”
Section: Xps Of Pts and Pts2supporting
confidence: 78%
“…Thermally assisted conversion (TAC) of pre-deposited Pt layers, sometimes referred to as vapor-phase selenization or soft selenization, is another synthesis approach which is capable of producing thin films of layered PtSe 2 at relatively low temperature. [14][15][16][17][18][19]32,34,49] In this method, a thin film of Pt, typically deposited by sputtering or evaporation onto SiO 2 /Si or quartz substrates, is reacted with Se vapor inside a tube furnace to produce polycrystalline thin films of PtSe 2 . The thickness of PtSe 2 can be controlled via the thickness of the pre-deposited Pt layer and the placement of the PtSe 2 can be controlled through using shadow masks or lithography to define the dimensions of the predeposited Pt.…”
Section: Synthesis Methodsmentioning
confidence: 99%
“…Studies have indicated that Ni forms an alloy in the contact region with PtSe 2 whereas Ti does not. [ 49 ] In conventional top‐contacted geometries the presence of an additional van der Waals gap provides a further impediment to the flow of charge carriers. Much research has focused on optimizing contact resistances in 2D‐materials‐based FETs and one promising approach is the use of edge contacts which lead to stronger hybridization and lower contact resistance.…”
Section: Sensing and (Opto‐)electronic Devicesmentioning
confidence: 99%
“…Chemical interactions of reactive metals with the underlying layered MC can affect interface structure as well as optoelectronic properties [124,125] . In addition, annealing can induce phase transformations at different material‐MC interfaces that are not otherwise favored at room temperature [126–129] . Understanding these interfacial phase transformations is essential for tailoring the physicochemical properties of layered MC devices.…”
Section: Structural and Chemical Transformations At Interfacesmentioning
confidence: 99%
“…[124,125] In addition, annealing can induce phase transformations at different material-MC interfaces that are not otherwise favored at room temperature. [126][127][128][129] Understanding these interfacial phase transformations is essential for tailoring the physicochemical properties of layered MC devices. In situ experiments are particularly useful for characterizing such transformations, and this section discusses several such efforts.…”
Section: Phase Transformations At Layered MC Interfacesmentioning
confidence: 99%